Peningkatan Konsumsi Susu Sapi untuk Anak Usia Dini Sebagai Pemenuhan Nutrisi di Desa Bedrug - Toni Diyan Pratama (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The early childhood period is a critical phase for children's physical, mental, and social development. During this stage, a balanced and adequate nutrition is essential to support their growth and overall health. Cow's milk is one of the valuable sources of nutrients. Consuming cow's milk during early childhood can help prevent various health issues, including anemia, stunting, obesity, infections, and allergies.However, not all children have equal access to consume cow's milk. Several factors influence the consumption of cow's milk among young children, such as availability, affordability, safety, cleanliness, and consumption habits. Therefore, efforts are needed to increase cow's milk consumption among young children while considering these aspects. Active participation from the community becomes a key element in developing local potential as a solution.In conclusion, the early childhood period is a crucial time for children's development, and cow's milk plays a significant role in providing essential nutrients. However, various factors affect the consumption of cow's milk, and addressing these factors requires active engagement from the community. By working together and collaborating with various stakeholders, we can create a sustainable and health-promoting environment that fosters increased cow's milk consumption among young children, ensuring a healthier and brighter future for the next generation.